2006
DOI: 10.1007/s10265-006-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and mating system of the threatened plant Kirengeshoma palmata (Saxifragaceae) in Korea

Abstract: The endangered herb Kirengeshoma palmata, from eastern Asia, has had its population severely reduced in number through habitat loss and fragmentation. All of the individuals within five subgroups at Mt. Baek-un-san, in the southern part of Korea, were genetically surveyed by allozyme analysis. Genetic diversity levels within subgroups were relatively high, and a consistently high outcrossing rate as well as a negligible biparental mating rate were confirmed by this study. Several groups of visibly connected ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 48 publications
2
19
2
Order By: Relevance
“…In addition to this, the high values of multi-population-level F IS (0.347) suggest that inbreeding would have decreased the N e of K. koreana populations, increasing the rate at which genetic diversity is lost due to random genetic drift. Our allozyme data seem to be in contrast with the previous study of Chang et al (2007), in which the authors suggested that K. koreana is a predominant outcrosser. In plants, F IS values of 0.300 or higher are indicative of mixed mating system with nearly equal amounts of selfing and outcrossing; thus, K. koreana is probably a mixedmating species.…”
Section: Extremely Low Levels Of Genetic Diversity In K Koreanacontrasting
confidence: 86%
See 4 more Smart Citations
“…In addition to this, the high values of multi-population-level F IS (0.347) suggest that inbreeding would have decreased the N e of K. koreana populations, increasing the rate at which genetic diversity is lost due to random genetic drift. Our allozyme data seem to be in contrast with the previous study of Chang et al (2007), in which the authors suggested that K. koreana is a predominant outcrosser. In plants, F IS values of 0.300 or higher are indicative of mixed mating system with nearly equal amounts of selfing and outcrossing; thus, K. koreana is probably a mixedmating species.…”
Section: Extremely Low Levels Of Genetic Diversity In K Koreanacontrasting
confidence: 86%
“…Small effective population size (N e ) has been suggested as the most important reason explaining the low levels of genetic diversity in narrow endemic species (e.g., Barrett and Kohn, 1991;Ellstrand and Elam, 1993;López-Pujol et al, 2013). Although neither recent nor reliable censuses are available for all the few extant populations of K. koreana, these are very small and scatteredly distributed, and are probably declining (Chang et al, 2007;J. M. Chung, pers.…”
Section: Extremely Low Levels Of Genetic Diversity In K Koreanamentioning
confidence: 97%
See 3 more Smart Citations